MDG Achievement and Debt Sustainability In HIPC and other Critically Indebted Developing Countries: Thoughts on an Assessment Framework - Kitabire, Damoni; Kabanda, Moses (New York, 2006)
This paper reviews the evidence on post-HIPC debt sustainability, 10 years on from the start of the HIPC process. In light of the evidence, it discusses the assessment of debt sustainability in the context of MDG achievement in low income countries. The evidence on post-HIPC debt sustainability is not encouraging, although the volumes of debt relief delivered by the HIPC initiative have been significant. An independent World Bank evaluation2 shows that debt ratios have deteriorated in 11 out of the 13 countries for which post-completion point data is available, with ratios having risen above the HIPC thresholds in 8 of them.